2012
DOI: 10.1155/2012/510391
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effect of Leaf Aqueous Extract ofCaesalpinia pyramidalisin Goats Naturally Infected with Gastrointestinal Nematodes

Abstract: Forty-eight goats naturally infected with gastrointestinal nematodes were randomly divided into four groups (n = 12): negative control (G1) (untreated), positive control (G2) (treated with doramectin, 1 mL/50 Kg b.w.), and G3 and G4 treated with 2.5 and 5 mg/Kg b.w. of a leaf aqueous extract of Caesalpinia pyramidalis (CP). Fecal and blood samples were regularly collected for the evaluation of fecal egg count (FEC), hematological and immunological parameters to assess the anthelmintic activity. In treated anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…1,4 Additionally, the aqueous leaf extract of P. pyramidalis has been used to treat gastrointestinal nematodes in goats, with promising results. 3 Pharmacologic studies have shown that aerial parts of the plant have anti-inflammatory, 18 antifungal, 7 and antimicrobial properties. 19 Its pollen has been proven to be toxic to honeybees ( Apis melifera ).…”
Section: Introductionmentioning
confidence: 99%
“…1,4 Additionally, the aqueous leaf extract of P. pyramidalis has been used to treat gastrointestinal nematodes in goats, with promising results. 3 Pharmacologic studies have shown that aerial parts of the plant have anti-inflammatory, 18 antifungal, 7 and antimicrobial properties. 19 Its pollen has been proven to be toxic to honeybees ( Apis melifera ).…”
Section: Introductionmentioning
confidence: 99%
“…The LBWs of the animals treated with the extract did not change significantly except those treated at the highest dose of 5mg/kg b.w. (Robson et al, 2012). In evaluation of in vivo anthelmintic activity using Boer goats, Worku et al (2009) observed that groups treated with wormwood and tobacco with added copper sulphate resulted in dramatic decreases in PCV values and related this to toxic effects of these plant extracts.…”
Section: 3mentioning
confidence: 99%
“…Among the biological activities of P . pyramidalis described in the literature, we can highlight the antibacterial [ 28 , 29 ], antifungal [ 30 ], antioxidant [ 31 ], gastroprotective [ 32 ], anti-inflammatory, antinociceptive [ 33 ] and antihelminthic [ 34 ] activities.…”
Section: Introductionmentioning
confidence: 99%